Enhancing students' self-efficacy, creativity, and performance through metacognitive blogging a reconfiguration for biology instruction - Lorenzana, Ruby A.; Yangco, Rosanelia T.; Muega, Maricris B. Acido; Gomez, Marie Grace A.; Pedrajita, Jose Q.; Pitagan, Ferdinand B. (Quezon City College of Education, University of the Philippines Diliman, 2022)
The study investigated the effect of metacognitive blogging teaching approach on the performance of students in Biology, their self-efficacy, and creativity as compared to the conventional method of teaching in two heterogenous fourth year high school biology classes. The research design used was a two-group, pretest-posttest quasi-experimental design employing metacognitive and conventional teaching approaches. Welch-2 sample t-test was used to determine significant differences in terms of creativity, self-efficacy, and performance in Biology between the two groups of students as they are exposed to two different teaching approaches. Path analysis served to test the effect of the teaching approaches on students' self-efficacy, creativity, and performance in Biology. Based on the study, it was revealed that there is a significant difference between the two groups in their posttest self-efficacy mean scores when the effect of pretest was controlled. Students exposed to the metacognitive blogging teaching approach had a significantly higher posttest creativity mean score and significantly higher posttest mean score in Biology than those taught using the conventional teaching approach. The teaching approach has the strongest significant effect on biology performance whereas self-efficacy has a strong significant effect on biology performance; creativity is significantly related to teaching approach but creativity has an indirect effect on biology performance. Creativity and self-efficacy are not significantly related. Findings of the study indicate that the metacognitive blogging teaching approach is effective in enhancing students' creativity and improving students' performance in Biology. Thus, the emergent framework for Biology Instruction using metacognitive blogging highlights these relationships as a result of path analysis. Further study on the use of blogs as a metacognitive tool may be done to enhance metacognition among learners. Researchers may also investigate other variables that may lead to the improvement of self-efficacy, creativity, and student performance in Biology.
Dissertation
Includes bibliographical references (108-112 leaves)
Keywords: Biology -- Study and Teaching (Secondary) -- Philippines .; Metacognition -- Study and learning (Secondary) -- Philippines; Learning strategies -- Philippines